THERMAL-HYDRAULICS PARAMETER ANALYSIS OF THE BANDUNG TRIGA 2000 REACTOR BASED ON CFD AND RELAP5/MOD3.2 - Reinaldy Nazar (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2011)
Reactor TRIGA 2000 Bandung is result of upgrading TRIGA Mark II reactor from nominal power of 1 MW becomes 2 MW and has been opened its the operation in the year 2000. In this period change of operation parameters had been occurred, especially the parameter related to thermo-hydraulic aspect, like the height of reactor core temperature and the formation of vapor bubble in the core, which is on the contrary with the safety aspect. Safety is the priority in the reactor operation, hence reactor core temperature and vapor bubble in core need to be reduced. One of methods to reduce the core temperature and vapor bubble formation is the operation at limited power of 1000 kW. To examine the safety margin of Bandung TRIGA 2000 reactor operation at 1000 kW power, the analysis of thermo-hydraulic characteristic have been carried out by theoretical study using computer code of CFD (Computational of Fluid Dynamics) and RELAP5/Mod3.2 (Reactor Excursion and Leak Analysis Program). The result of the study indicates that reactor reaches steady state condition at 1000 kW power in 1500 seconds after critical condition, and maximum temperature of reactor core is in C4 position, whereas the maximum temperature of fuel center, cladding, and cooling water at related fuel are 529.35 °C, 103.12 °C, and 90.67 °C, respectively. Maximum temperature of cladding and primary cooling water at related fuel are below saturation temperature (112.4 °C), so the sub-cooled boiling or bubbling of saturation and vapor bubble formation can be predicted not to be happened. Besides when the reactor was operated at 1200 kW and 1250 kW power was obtained the maximum temperature of fuel cladding are 111.04 °C and 115.53 °C, respectively. This thing informs that, when the reactor was operated up to 1200 kW power sub-cooled boiling has not happened, but when the reactor was operated at 1250 kW power has started the happening of the sub-cooled boiling and the formation of vapour bubble. The result of this study can be used as a valuable information in operating Bandung TRIGA 2000 reactor at the limited power of 1000 kW and revising safety analysis report (SAR) of Bandung TRIGA 2000 reactor.Keywords: Bandung TRIGA 2000 reactor, 1000 kW limited power, thermal-hydraulic aspect, computer code of CFD, computer code of RELAP5/Mod3.2.   Reaktor TRIGA 2000 Bandung merupakan hasil upgrading dari reaktor TRIGA Mark II berdaya nominal 1 MW menjadi 2 MW dan telah diresmikan pengoperasiannya pada tahun 2000. Dalam periode tersebut telah terjadi perubahan parameter operasi, terutama parameter yang berkaitan dengan aspek termohidrolik, seperti suhu teras reaktor yang tinggi dan menyebabkan terjadi pembentukan gelembung uap di dalam teras. Hal ini bertentangan dengan aspek keselamatan. Mengingat masalah keselamatan merupakan hal yang utama, maka perlu dilakukan penurunan suhu teras reaktor dan pengurangan pembentukkan gelembung uap di dalam teras, diantaranya dengan mengoperasikan reaktor TRIGA 2000 Bandung pada daya terbatas 1000 kW. Untuk mengetahui tingkat keselamatan pengoperasian reaktor TRIGA 2000 Bandung pada daya 1000 kW, dilakukan analisis karakteristik termohidrolik melalui kajian teoritik menggunakan program computer Computational Fluid Dynamics (CFD) dan RELAP5/Mod3.2 (Reactor Excursion and Leak Analysis Program). Hasil kajian menunjukkan bahwa reaktor mencapai kondisi tunak pada daya 1000 kW setelah 1500 detik reaktor kritis, suhu maksimum bahan bakar di dalam teras reaktor berada di posisi C4 dimana suhu maksimum pusat bahan bakar 529,35 °C, suhu maksimum kelongsong bahan bakar 103,12 °C, dan suhu maksimum pendingin pada posisi bahan bakar terkait 90,67 °C. Suhu maksimum kelongsong bahan bakar dan suhu maksimum pendingin yang diperoleh berharga jauh di bawah suhu saturasi 112,4 °C, sehingga pendidihan prajenuh (sub-cooled boiling) atau pendidihan saturasi dan pembentukan gelembung uap di dalam teras diprediksi tidak terjadi. Selain itu ketika reaktor dioperasikan pada daya 1200 kW dan 1250 kW diperoleh suhu maksimum kelongsong bahan bakar berturut-turut 111,04 °C and 115,53 °C. Hal ini menginformasikan bahwa ketika reaktor dioperasikan hingga daya 1200 kW belum terjadi pendidihan prajenuh (sub-cooled boiling) atau pendidihan saturasi, tetapi ketika reaktor dioperasikan pada daya 1250 kW telah mulai terjadi pendidihan prajenuh (sub-cooled boiling) atau pendidihan saturasi dan pembentukan gelembung uap. Hasil kajian ini dapat menjadi informasi dalam mengoperasikan reaktor TRIGA 2000 pada daya terbatas 1000 kW dan merevisi Laporan Analisis Keselamatan (LAK) reaktor TRIGA 2000 Bandung. Kata kunci: reaktor TRIGA 2000 Bandung, daya 1000 kW, aspek termohidrolik, program komputer CFD, program computer RELAP5/Mod3.2.